Intraoperative Troponin Elevation in Liver Transplantation Is Independently Associated With Mortality: A Prospective Observational Study. Issue 5 (8th April 2020) - Vilchez‐Monge, Almudena L.; Garutti, Ignacio; Jimeno, Concepción; Zaballos, Matilde; Jimenez, Consuelo; Olmedilla, Luis; Piñeiro, Patricia; Duque, Patricia; Salcedo, Magdalena; Asencio, Jose M.; Lopez‐Baena, Jose A; Maruszewski, Przemyslaw; et al.
Abstract : Intraoperative factors implicated in postoperative mortality after liver transplantation (LT) are poorly understood. Because LT is a particularly demanding procedure, we hypothesized that intraoperative myocardial injury may be frequent and independently associated with early postoperative outcomes. We aimed to determine the association between intraoperative high‐sensitivity troponin (hsTn) elevation during LT and 30‐day postoperative mortality. A total of 203 adult patients undergoing LT were prospectively included in the cohort and followed during 1 year. Advanced hemodynamic parameters and serial high‐sensitivity troponin T (hsTnT) measurements were assessed at 6 intraoperative time points. The optimal hsTnT cutoff level for intraoperative troponin elevation (ITE) was identified. Patients were classified into 2 groups according to the presence of ITE. Independent impact of ITE on survival was assessed through survival curves and multivariate Cox regression analysis. Intraoperative cardiac function was compared between groups. Troponin levels increased early during surgery in the ITE group. Troponin values at abdominal closure were associated with 30‐day mortality (area under the receiver operating caracteristic curve, [AUROC], 0.73; P  = 0.005). Patients with ITE showing values of hsTnT ≥61 ng/L at abdominal closure presented higher 30‐day mortality (29.6% versus 3.4%; P  < 0.001). ITE was independently associated with 30‐day mortality (hazard ratio, 3.8; 95% confidence interval, 1.1‐13.8; P  = 0.04) and with worse overall intraoperative cardiac function. The hsTnT upper reference limit showed no discriminant capacity during LT. Intraoperative myocardial injury identified by hsTn elevation is frequently observed during LT, and it is associated with myocardial dysfunction and short‐term mortality. Determinations of hsTn may serve as a valuable intraoperative monitoring tool during LT.